PENGARUH HARAPAN KONSELI DAN PERILAKU NONVERBAL KONSELOR TERHADAP KEBERHASILAN LAYANAN KONSLEING INDIVIDUAL - Arias, Alberta Caecaria; Mudjijanti, Fransisca (Educatio Vitae, 2019)
The purpose of this study is to analyze The Influence of counselee’s expectations and councelor’s non verbal behavior on individual counseling services successness. Population of this study is SMA Negeri 6 Madiun’s student, who have conducted individual counseling services from July 2017 to April 2018 with 75 students in total. Sampling technique that be used by writer is saturated sampling, therefore the number of samples in this study are 75 students. The data is analyzed by using the technique of doubled regression. The model of regression equality Y=21,400+0,341X1+0,232X2. It gives the results of hypotheses experiment as 1.) The expectation of someone who counsults gives an influence to the success of accepted individual's counseling process significantly. It because of the discovery which tells that quantification t > tabel t = (2,848 > 2,000) ; 2.) The councelor’s non verbal behavior gives a significant influence to the success of counseling process of accepted individual. It is proved by the evidence of quantification t > tabel t = (2,259 > 2,000); 3.) The prospect of consulted person and nonverbal behavior effecting to the success of counseling process of accepted individual. It is known by the proof of quantification F > tabel F = (8,964>3,12) Keywords: Counselee’s Expectations, Councelor’s Non Verbal Behavior.